2014
DOI: 10.4103/2141-9248.144925
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of human immunodeficiency virus, hepatitis B, hepatitis C, syphilis, and co-infections among antenatal women in a tertiary institution in South East, Nigeria

Abstract: Background:Sexually transmitted infections and human immunodeficiency virus (HIV)/AIDS are a major public health concern owing to both their prevalence and propensity to affect offspring through vertical transmission.Aim:The aim was to determine the seroprevalence of HIV, hepatitis B virus (HBV), hepatitis C virus (HCV), syphilis, and co-infections among antenatal women in Enugu, South-East Nigeria.Materials and Methods:A retrospective study of antenatal women at the University of Nigeria Teaching Hospital, En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 20 publications
1
22
6
Order By: Relevance
“…Similar trend was found in this study where higher positivity 5.5% was detected among unemployed pregnant women. This is similar to study by Ikeako et al in west Nigeria which indicated that unemployed pregnant women formed bulk of positive cases [ 31 ]. This may be explained by the low economic status initiating women to multiple sexual partnerships and unprotected sex thus making them vulnerable to STIs [ 21 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar trend was found in this study where higher positivity 5.5% was detected among unemployed pregnant women. This is similar to study by Ikeako et al in west Nigeria which indicated that unemployed pregnant women formed bulk of positive cases [ 31 ]. This may be explained by the low economic status initiating women to multiple sexual partnerships and unprotected sex thus making them vulnerable to STIs [ 21 ].…”
Section: Discussionsupporting
confidence: 91%
“…In this study majority of the women were sexually active thus predisposing them to risk of acquiring HBV infection [ 30 , 31 ]. A higher rate of HBsAg was detected in age group 20-24 years (4.3%) which is the second peak of HBV infection in Kenya [ 8 ]).…”
Section: Discussionmentioning
confidence: 99%
“…This rate was higher than that reported previously from a national hospital in Dar es Salaam, Tanzania [12]. Furthermore, the prevalence of HBV/HIV co-infection among pregnant women found in our study was higher than the previous reports in Nigeria (0.24%), Ethiopia (0.6%) and Cameroon (1.5%) [24, 33, 34]. However, the prevalence of HBsAg in the current study was lower than that reported from a recent study among pregnant women in South Africa (3.1%) [35].…”
Section: Discussioncontrasting
confidence: 88%
“…Prevalence of HCV infection varies across different regions and populations [ 25 ]. In Africa, prevalence of HCV infection reported so far has focused on a specific group of the population mostly relying on the error-prone antibody testing method [ 9 , 10 , 26 , 27 ]. In this study, participants were first screened against the presence of HCV antibodies using rapid diagnostic strips.…”
Section: Discussionmentioning
confidence: 99%